Plasma leptin and vascular endothelial growth factor (VEGF) in normal subjects at high altitude (5050 m). (17th July 2013) - Morici, G.; Bonanno, A.; Licciardi, A.; Valli, G.; Passino, C.; Bonardi, D.; Locorotondo, N.; Profita, M.; Palange, P.; Cogo, A.; Bonsignore, M.R.
Abstract: Context: High altitude (HA) is a model of severe hypoxia exposure in humans. We hypothesized that nocturnal hypoxemia or acute maximal exercise at HA might affect plasma leptin and VEGF levels. Objectives: Plasma leptin, VEGF and other metabolic variables were studied after nocturnal pulse oximetry and after maximal exercise in healthy lowlanders on the 3rd-4th day of stay in Lobuche (5050 m, HA) and after return to sea level (SL). Results: Leptin was similar at SL or HA in both pre- and post-exercise conditions. Pre-exercise VEGF at HA was lower, and cortisol was higher, than at SL, suggesting that nocturnal intermittent hypoxia associated with periodic breathing at HA might affect these variables. Conclusions: Leptin levels appear unaffected at HA, whereas nocturnal hypoxic stress may affect plasma VEGF. Future HA studies should investigate the possible role of nocturnal intermittent hypoxemia on metabolism.